2014
DOI: 10.1103/physreva.90.042117
|View full text |Cite
|
Sign up to set email alerts
|

Pauli equation for a charged spin particle on a curved surface in an electric and magnetic field

Abstract: We derive the Pauli equation for a charged spin particle confined to move on a spatially curved surface S in an electromagnetic field. Using the thin-layer quantization scheme to constrain the particle on S, and in the transformed spinor representations, we obtain the well-known geometric potential Vg and the presence of e −iϕ , which can generate additive spin connection geometric potentials by the curvilinear coordinate derivatives, and we find that the two fundamental evidences in the literature [Giulio Fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…. In other words, the presence of the spin degree of freedom can influence the geometric effects of the curved surface [33]. Besides, the termh 2R 8m has no contribution to the scalar potential as Ricci scalar vanishes in the thin-layer procedure.…”
Section: Effective Equation In Curved 2d Space With Spin Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…. In other words, the presence of the spin degree of freedom can influence the geometric effects of the curved surface [33]. Besides, the termh 2R 8m has no contribution to the scalar potential as Ricci scalar vanishes in the thin-layer procedure.…”
Section: Effective Equation In Curved 2d Space With Spin Connectionmentioning
confidence: 99%
“…In the language of quantum field theory, it can also be viewed as a non-Abelian gauge field generated by local Lorentz transformations [31]. In the 2D curved space, the motion of a fermion should embody the effect of this gauge field [32].Several studies have considered the contribution of the spin connection to the dynamics on curved surfaces [33][34][35], however, the explicit effective SOI Hamiltonian from curvature has not be given. In addition, it has been found that the SOI from electric fields can also be reformulated in terms of non-Abelian gauge fields [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Geometry can also induce a reminiscent of the Hall effect [5]. Related important investigations can also be found in the literature, for instance: the quantum Hall effect near conical singularities [6] and investigations taking into account the Pauli equation for a charged spin particle on a curved surface with externally applied fields [7,8]. Recent developments can also be found in [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…An application in this case can be viewed in [9], where important features concerned to the quantum Hall states on surfaces with conical singularities has been presented. The version for Pauli equation for a charged spin particle on a curved surface in an electric and magnetic field has been addressed in [10]. An application which followed this reference can be viewed in [11].…”
Section: Introductionmentioning
confidence: 99%